Bilateral congenital pulmonary airway malformation in an extremely preterm infant. Issue 4 (15th April 2021) - Chandrasekaran, Preethi; Goergen, Stacy; Robinson, Alice; Moghimi, Ali; Malhotra, Atul
Abstract : We present the case of a baby boy, with antenatal finding of bilateral enlarged echogenic lungs, who developed severe postnatal respiratory failure. Two important differential diagnoses, which have an impact on antenatal and postnatal management, are discussed. Fetal ultrasound, MRI and postmortem MRI images are presented and findings correlated with the autopsy findings.